Design, Construction, and Early Results of a Formal Local Revision Knee Arthroplasty Registry - Visvanathan, Aravinthan; Wilson, Christopher; Jackman, Emma; Wong, Geraldine; Krishnan, Jegan (The Journal of Knee Surgery, 2020)
National registries for primary and revision knee arthroplasty in Australia, New Zealand, and Europe have been successful in ensuring quality control and providing information to drive crucial research. However, they face challenges in delivering the granularity of data useful at a local hospital level. Our aim was to address these challenges by designing and initiating a local revision knee arthroplasty registry and combining the data with national figures to better evaluate the types of revisions undertaken, and improve patient outcomes and care. All revision knee arthroplasty cases in our center were analyzed from April 2014 to December 2015 using our standardized diagnostic algorithm. Information such as reason and type of revision was collected. Results were compared with Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) data. Primary outcome was comparison against our center's historical data between January 1999 and December 2013 and secondary outcome was comparison against national data prior to and after our intervention. Between April 2014 and December 2015, our center performed 35 revision knee arthroplasties. When compared with our center's historical data, we observed lower rates of revision knee arthroplasties due to “pain” (14.2 vs. 36.7%) with corresponding lower rates of patella button only revision (8.6 vs. 39.2%). Compared with national data before our intervention, we had lower revision rates from infection (14.2 vs. 22.3%) and loosening/lysis (11.4 vs. 29.2%). We undertook more minor revisions (45.7 vs. 30.5%) and similar total revisions (25.7 vs. 25.3%). Similar trends were seen in comparison to national data after our intervention. Our study shows that a local registry can be designed and successfully implemented for revision knee arthroplasty surgery. Data can be easily compared with historic and current hospital and national registry data trends to assess quality and robustness of revision arthroplasty programs. Our early results suggest our center has succeeded in reducing incidences of major revisions, complications, and the risk of re-revision surgery. This will improve the quality of our service with a significant cost reduction for our local health care budget.
Keywords: revision; registry; knee; arthroplasty